CRL's foreign newspaper database - Smets, Kristine, 1963-; Pilecky-Dekajlo, Adriana, 1958- (Center for Research Libraries, 1998)
Searchable online index of foreign newspapers held by the Center for Research Libraries; constructed from a bibliography originally compiled by Kristine Smets and Adriana Pilecky-Dekajlo and published in hardcopy with title: Foreign newspapers held by the Center for Research Libraries.